Dampak Integrasi Ekonomi Indonesia–China terhadap Arus Investasi dan Neraca Dagang Nasional - Dewi Ari Ani; Bulan Karima Nurani (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
The emergence of various commonwealths, alliances, and other forms of inter-state organizations has significantly influenced the course of existing international cooperation. Cooperation between countries serves not only as a platform for strengthening political and social relations but also as a key element in meeting domestic needs that cannot be met independently through a country's self-help programs. Therefore, international cooperation is an aspect that is continuously maintained and strengthened by countries worldwide. Historically, cooperative relations between countries have generally developed as a result of the increasing ties that have existed over time. This dynamic involves various sectors, including economics, trade, and investment, further demonstrating the crucial role of international relations in a country's progress. Countries involved in this cooperation benefit each other, both in meeting domestic needs and in increasing their economic capacity through innovation and collaboration. The data sources for this study were obtained from documents obtained through internet media, which were then processed and analyzed to gain a deeper understanding of the impact of international cooperation. This study uses a quantitative approach, focusing on the analysis of investment flows into the country. Increased investment flows will drive higher growth in goods production, which in turn will strengthen trade activities, including exports to destination countries such as China. Furthermore, increased investment also contributes to the growth of Gross Domestic Product (GDP) in developing countries. This GDP increase will positively impact Indonesia's trade balance, particularly with China, one of its major trading partners in the Asian region.